2013
DOI: 10.1080/13614568.2013.806960
|View full text |Cite
|
Sign up to set email alerts
|

Progressor: social navigation support through open social student modeling

Abstract: The increased volumes of online learning content produced two problems: how to help students to find the most appropriate resources and how to engage them in using these resources. Personalized and social learning have been suggested as potential ways to address these problems. Our work presented in this paper combines the ideas of personalized and social learning in the context of educational hypermedia. We introduce Progressor, an innovative Web-based tool based on the concepts of social navigation and open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 24 publications
1
41
0
1
Order By: Relevance
“…• Other kinds of systems such as social navigation systems (e.g., Educo [58] or Progressor [35]) that provide information about how peers have used and progressed through the learning resources, and thus support reflection of one's own working and progress.…”
Section: Defining Smart Learning Contentmentioning
confidence: 99%
“…• Other kinds of systems such as social navigation systems (e.g., Educo [58] or Progressor [35]) that provide information about how peers have used and progressed through the learning resources, and thus support reflection of one's own working and progress.…”
Section: Defining Smart Learning Contentmentioning
confidence: 99%
“…OSLM has been demonstrated to produce different effects in both engagement and navigational patterns. For example [15,16] in different studies consistently found that by showing the models of peer learners, students covered more topics in the system, reached higher success rates in self-assessment problems, and that strong students lead in system exploration. Our later work confirms these findings and reveals some other effects.…”
Section: Related Workmentioning
confidence: 98%
“…People tend to follow the footsteps of other people who have similar interests. Using this natural tendency, a document may be indexed in the existing hyperspace by a community of users (Wexelblat and Maes, 1999;Hsiao et. Al., 2013).…”
Section: Discussionmentioning
confidence: 99%